WORK LIFE BALANCE DENGAN STRES KERJA PADA ANGGOTA POLISI WANITA Di POLRES SURABAYA: WORK LIFE BALANCE DENGAN STRES KERJA PADA ANGGOTA POLISI WANITA Di POLRES SURABAYA - Purwaningtyas, Fifin Dwi; Pertamaputri, Adylia Nuroktavia (Journal of Gender Equality and Social Inclusion (gesi), 2024)
Work-life balance is an individual's ability to manage the balance between work demands and family life or daily life which can influence work stress. This research was conducted to determine the relationship between work-life balance and work stress in female police officers. The research location chosen was the Tanjung Perak Harbor Police with a sample size of 29 people. The data collection technique uses a 17-item work-life balance questionnaire and a 16-item Work Stress scale in the form of a Google form. From the results of data analysis using the product-moment correlation test, the results show a significance value of 0.000 < 0.05 and the results of the correlation coefficient value are -0.777, indicating a high level of correlation strength with a negative sign which means the opposite, which means the higher the work-life balance, the lower the work stress. experienced.